Sex as slavery?: understanding private wrongs - Brysk, Alyson (Human rights review, 2011)
The era of globalization has been accompanied by an increased awareness of private wrongs as well as acceleration of many forms of cross-border labor exploitation. The essay explores how refined distinctions between forced and free sex work could improve anti-trafficking policies. It addresses the understudied linkages between other forms of migration and sexual exploitation and suggests a triage approach to all forms of labor exploitation—based on harms rather than type of labor or victim. A better understanding of freedom, sex, and development will allow us to expand a human rights approach to these private wrongs. The best anti-trafficking policy is one of universal, indivisible human rights. Victims of sexual exploitation need the same things as all migrants and all workers—recognition, monitoring, resources, access to justice, and organization.